Sistem Informasi Transaksi Pembayaran Tagihan Air Di PDAM - Melin Sitorus; Desi Triani Sipayung (Forum Kerja Sama Penddikan Tinggi (FKPT), 2021)
PDAM is a regional company engaged in the management of drinking water and the management of dirty water facilities. One of the main activities in PDAM is providing services to customers. Currently, to get services regarding billing information, report stand meter numbers and report complaints against PDAM services, customers must come to the head office so that the service process is not optimal and inefficient. To provide optimal service, it is necessary to develop a better information system using information technology facilities that can be accessed by customers easily.